1999
DOI: 10.1097/00000658-199904000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Nutritional Supplementation With Key Nutrients in Patients With Critical Illness and Cancer

Abstract: This meta-analysis has demonstrated that nutritional support supplemented with key nutrients results in a significant reduction in the risk of developing infectious complications and reduces the overall hospital stay in patients with critical illness and in patients with gastrointestinal cancer. However, there is no effect on death. These data have important implications for the management of such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
189
1
29

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(222 citation statements)
references
References 36 publications
3
189
1
29
Order By: Relevance
“…While early studies and meta-analyses suggested reduced infection rates, ICU length of stay, and duration of mechanical ventilation, in both medical and surgical patients in a general ICU [59], Heyland and colleagues found a modest reduction in hospital length of stay, particularly in medical patients [60]. Furthermore and according to ASPEN Guidelines, current evidence does not support the use of enteral fish oil administration, particularly in medical ICU patients, due to heterogeneity of studies, variety of experimental and commercial lipid formulations, variable dosage of individual components, and increased costs [55].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…While early studies and meta-analyses suggested reduced infection rates, ICU length of stay, and duration of mechanical ventilation, in both medical and surgical patients in a general ICU [59], Heyland and colleagues found a modest reduction in hospital length of stay, particularly in medical patients [60]. Furthermore and according to ASPEN Guidelines, current evidence does not support the use of enteral fish oil administration, particularly in medical ICU patients, due to heterogeneity of studies, variety of experimental and commercial lipid formulations, variable dosage of individual components, and increased costs [55].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Six major meta-analyses reviewing these trials in surgical and trauma patients have been published (64)(65)(66)(67)(68)(69) . The two most recent studies by Marik et al and Drover et al describe both substantial reduction in post-operative complications and a shorter LOS with the use of arginine administration.…”
Section: Arginine Supplementation In Surgical Patientsmentioning
confidence: 99%
“…Z kolei Heys i wsp. [16] przedstawili obszerną metaanalizę, z której wyodrębniono 6 badań porównujących dojelitowe leczenie żywieniowe typu immunonutrition (arginina, kwasy omega-3, RNA, bez glutaminy) z żywieniem standardowym u chorych operowanych z powodu nowotworów przewodu pokarmowego. W grupie otrzymującej immunonutrition stwierdzono istotnie mniejszą liczbę powikłań pooperacyjnych (zapaleń płuc, ropni wewnątrzbrzusznych, zakażeń rany, zakażeń septycznych) oraz krótszy czas hospitalizacji w porównaniu z grupą kontrolną.…”
Section: Zalecenia Espen Dla Chorych Poddawanych Zabiegom Chirurgicznymunclassified
“…Więk-szość badań wykonywano jednak w niejednolitych grupach chorych po różnych urazach, u chorych poddawanych zabiegom chirurgicznym lub po oparzeniach, co znacznie utrudniło interpretację uzyskanych wyników. W kilku metaanalizach opartych na grupach chorych, u których stosowano złożone preparaty żywieniowe zawierające glutaminę, argininę oraz nukleotydy, stwierdzono, że immunomodulujące żywienie dojelitowe w porównaniu z żywieniem standardowym powoduje istotne zmniejszenie liczby powikłań infekcyjnych, skraca czas pobytu chorych na OIT oraz w szpitalu [16][17][18][19]. Immunonutrition nie miało jednak wpływu na śmiertelność w tej grupie chorych.…”
Section: Intensywna Terapiaunclassified